A instrução pública, a educação da mulher e a formação de professores nos jornais partidários de Porto Alegre/RS (1869-1937) - Gonçalves, Dilza Pôrto (2013)
This thesis comprises a reflection, from discourses about public education, women's education and teacher training, published in journals supporters in Porto Alegre / RS (1869-1937). The paper is enrolled in the scientific field of Cultural History and the History of Education, passing through the bias in political history. The input document is used are the journals: The Reformation which is an organ of the Liberal Party, the Conservative organ of the Conservative Party and the Federation, the national Republican Party Riograndense. Through the content analysis method developed by Bardin (1977), which is used to understand the speeches, taking into account the political, social and cultural scenario in which they were produced. In order to that the significance of these speeches to the social group that produced them were related, the editors of journals supporters also linked to public education and teacher training. However, what matters in this paper is not the political debate in itself, but as this debate reflects the discourses and representations produced on public education, women's education, and especially on the Normal School / District School / School Complementary School / Normal School / Normal School General Flores da Cunha, in the partisan press. In speeches on women education attention was drawn to the writings of Anne Aurora Amaral Lisbon in The Reformation. Graduated from the the Normal School of Porto Alegre, wrote several articles about education and especially on the political participation of women.As periodicals are chosen by the partisans, it is important to bear in mind that the writers build a partisan speech. But it is important to emphasize that even having a definite ideological stance; the journal has important qualities for historical research, especially from the perspective of cultural history and constitute archives of the everyday life of a society. In theory, what it is wanted to address is how this "image" of "model school" for the the Normal School was constructed and how these discourses partisans contributed to this construction. Furthermore, we can see what kind of education was designed for the population and especially for women from Porto Alegre, perhaps for women from Rio Grande do Sul